Publications of the Modern Language Association of America, Menasha, Wisconsin, vol. LXIII, 1948. - Boyd-Bowman, Peter (Nueva Revista de Filología Hispánica (NRFH), 1950)
Se reseñó: Publications of the Modern Language Association of America, vol. LXIII, 1948.